Total Hysterectomy as Treatment for Recurrent Chronic Pyometra in Mares With Total Cervical Adhesion–Case Report - Prestes, Nereu Carlos [UNESP]; Medrado, Felipe Erison [UNESP]; Rodrigues, Lucas Troncarelli [UNESP]; Canuto, Lucas Emanuel Ferreira [UNESP]; Lemos Motta, Jéssica Cristina [UNESP]; Segabinazzi, Lorenzo Garrido [UNESP]; Alvarenga, Marco Antonio [UNESP] (Elsevier, 2018)
Radical hysterectomy is indicated as a last resource in pyometra that does not respond to pharmacological therapy, uterine torsion with vascular involvement and onset of necrosis, neoplasia, ruptures of impossible synthesis and rarely, segmental aplasia with accumulation of secretion. The incidence of pyometra is multifactorial, being an unusual condition in this species. Generally, it is originated by failure of the physiological draining of the uterine fluid, which may be due to the presence of cervical adherences or to a sinuous or irregular cervical canal, as well as due to its stenosis. The diagnosis is conducted by a complete gynecological exam, which consists of rectal palpation, ultrasound examination, culture and antibiogram of the content, and can be complemented by uterine biopsy when it is possible. Differential diagnosis should be conducted to confirm the absence of gestation, mucometra and pneumometra. The present report is about an equine female, Mangalarga breed, 23 years old, body weight of 470 kg, diagnosed with recurrent chronic pyometra that was unsolved by conventional methods, and surgical intervention was performed for hysterectomy as a treatment of selected.
Keywords: Equine; Fertility rate; Pyometra; Uterine infection; Uterine problem